2008
DOI: 10.1111/j.1749-4486.2008.01666.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of psycho‐social factors and survival in head and neck cancer

Abstract: There appears to be some association between selected psycho-social factors and long-term survival from head and neck cancer. However this relationship is currently neither strong nor proven, requiring examination by multi centred trials with standardisation of research definitions and methodologies, and examination of post-treatment psycho-social factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
2
30
1
Order By: Relevance
“…These results are in line with a study which has identified gender differences with regard to pain, with higher scores for females 20 . The relationship between very severe pain and low educational level shown by this study is in line with other findings, where pain intensity was related to low educational level 21,22 .…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with a study which has identified gender differences with regard to pain, with higher scores for females 20 . The relationship between very severe pain and low educational level shown by this study is in line with other findings, where pain intensity was related to low educational level 21,22 .…”
Section: Discussionsupporting
confidence: 93%
“…6,18 Others, however, point out that even when some association between selected psychosocial factors and survival exists, the impact of HRQL on survival in patients with H&N cancer is not definitely proven. 24 Consequently, in patients with H&N cancers, prognostic impact of HRQL data, is far from being elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Interdisciplinary research teams, of which nurses are often leaders, commonly conduct QOL studies [5 ,8 ,9-11]. Many studies [12][13][14][15][16] identify pretreatment factors that predict QOL and other outcomes such as survival after treatment.…”
Section: Patient Experiencementioning
confidence: 99%